Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.18632/oncotarget.26736
|View full text |Cite
|
Sign up to set email alerts
|

The BET-bromodomain inhibitor JQ1 renders neuroblastoma cells more resistant to NK cell-mediated recognition and killing by downregulating ligands for NKG2D and DNAM-1 receptors

Abstract: Low expression of ligands for NK cell-activating receptors contributes to neuroblastoma (NB) aggressiveness. Recently, we demonstrated that the expression of MYCN, a poor prognosis marker in NB, inversely correlates with that of activating ligands. This indicates that MYCN expression level can predict the susceptibility of NB cells to NK cell-mediated immunotherapy and that its downregulation can be exploited as a novel therapeutic strategy to induce the expression of activating ligands. Here we evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Our bulk RNA-seq data revealed that JQ1(+) treatment led to a downregulated NK cell cytolytic response, which impacted NK cell killing of cancer cells, in part through the downregulation of NK cell activating receptors. Consistent with these findings, JQ1 has been shown to downregulate target ligands in neuroblastoma cells and downregulate NK cell activation receptors NKG2D and DNAM-1 on NK cells (40). Unlike inflammatory function, where both BRD2 and BRD4 were found to play a role in the regulation of cytokine genes, we show that when only BRD4 is perturbed do we see a significant reduction in the ability of NK cells to eliminate cancer target cells.…”
Section: Discussionsupporting
confidence: 83%
“…Our bulk RNA-seq data revealed that JQ1(+) treatment led to a downregulated NK cell cytolytic response, which impacted NK cell killing of cancer cells, in part through the downregulation of NK cell activating receptors. Consistent with these findings, JQ1 has been shown to downregulate target ligands in neuroblastoma cells and downregulate NK cell activation receptors NKG2D and DNAM-1 on NK cells (40). Unlike inflammatory function, where both BRD2 and BRD4 were found to play a role in the regulation of cytokine genes, we show that when only BRD4 is perturbed do we see a significant reduction in the ability of NK cells to eliminate cancer target cells.…”
Section: Discussionsupporting
confidence: 83%
“… 115 In neuroblastoma, JQ1 impairs the expression of ULBP1–3 ligands for NKG2D activating receptor by inhibiting the transcriptional regulation of MYC and tumor protein P53 (TP53), thereby rendering NB cell lines more resistant to NK cell-mediated killing. 116 These studies demonstrate the dual role of BETs in antitumor immunity, depending on MYC status and cancer type.…”
Section: Introductionmentioning
confidence: 81%
“…[75]). For example, neuroblastoma tumours have a low expression of ligands (PVR, nectin-2, MICA, MICB and ULBPs) for NK cellactivating receptors DNAM-1 and NKG2D [76,77]. MYCN expression can also modulate susceptibility of neuroblastoma to NK-mediated killing: upregulation of MYCN in an inducible cell line led to downregulation of NK-activating ligands, resulting in reduced NKmediated lysis of the tumour cells [57].…”
Section: Escaping Nk Cellsmentioning
confidence: 99%